2013
DOI: 10.7899/jce-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of accurate blood pressure measurement procedures in chiropractic students

Abstract: Objective: Blood pressure measurement is a basic clinical procedure. However, studies have shown that many errors are made when health care providers acquire blood pressure readings. Our study assessed knowledge of blood pressure measurement procedures in chiropractic students. Methods: This was an observational, descriptive study. A questionnaire based on one created by the American Heart Association was given to 1st, 2nd, 3rd, and final year students (n ¼ 186). A one way ANOVA was used to analyze the data. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
2
5
0
5
Order By: Relevance
“…As with nursing and other nonphysician healthcare professionals, we believe strongly that competency testing of physicians should be ongoing as well. Our findings are consistent with existing studies performed outside the United States in medical, nursing, chiropractic, and pharmacy students, making it likely that this is an international problem in need of a solution and not only a domestic one . One successful strategy for mitigating the loss of competence of BP measurement skills after initial training among medical students in Turkey included refresher training in the third year followed by performing BP measurements on real patients …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As with nursing and other nonphysician healthcare professionals, we believe strongly that competency testing of physicians should be ongoing as well. Our findings are consistent with existing studies performed outside the United States in medical, nursing, chiropractic, and pharmacy students, making it likely that this is an international problem in need of a solution and not only a domestic one . One successful strategy for mitigating the loss of competence of BP measurement skills after initial training among medical students in Turkey included refresher training in the third year followed by performing BP measurements on real patients …”
Section: Discussionsupporting
confidence: 88%
“…It is, therefore, critical that medical students attain mastery of this procedure during medical school, when they are initially taught how to perform it. However, studies from many countries have demonstrated that medical, nursing, chiropractic, and pharmacy students do not obtain mastery of the skills needed to measure BP competently while in school . We are not aware of any published studies assessing US medical students’ BP measurement technique.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, only about 48% of the participants were aware of the size of the cuff bladder required for accurate measurement of blood pressure. These results are consistent to the studies in Hispania [24], USA [29] and Australia [19] among nursing students, where 32.8%, 45 % and 57% were aware of the estimating cuff size required in blood pressure measurement respectively. Nurse should ensure that the cuff bladder length is at least 75% of arm circumference, and BP cuff bladder of 37%-50% of the patient's arm circumference (a length-to-width ratio of 2:1) [16].…”
Section: Discussionsupporting
confidence: 90%
“…Measuring arterial blood pressure provided important information about the overall health status of the patient, for example, the systolic pressure provides a data base about the condition of the heart, arteries and the arterioles. The diastolic pressure indicates vessel resistance, the difference between the systolic and diastolic pressure provides information about cardiac output [Crosley et al, 2013]. Accurate blood pressure measurement is indispensable for successful detection and management of hypertension.…”
Section: Introductionmentioning
confidence: 99%